2000
DOI: 10.1359/jbmr.2000.15.12.2315
|View full text |Cite
|
Sign up to set email alerts
|

A Negative Search for a Paramyxoviral Etiology of Paget's Disease of Bone: Molecular, Immunological, and Ultrastructural Studies in U.K. Patients

Abstract: Paget's disease of bone is a common bone disease characterized by increased and disorganized bone remodeling at focal sites throughout the skeleton. The etiology of the disease is unresolved. A persistent viral infection has long been suggested to cause the disease. Antigen and/or nucleic acid sequences of paramyxoviruses (in particular measles virus [MV], canine distemper virus [CDV], and respiratory syncytial virus [RSV]) have been reported in pagetic bone by a number of groups; however, others have been una… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
71
2
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(76 citation statements)
references
References 56 publications
0
71
2
3
Order By: Relevance
“…No wild-type sequences were obtained, which argues against vaccination being responsible for a delay in OS presentation [151]. In PD, some nucleotides differed from the published vaccine strain, although when five of these were examined more closely [152], they were due to errors in the sequence used for comparison. Others have not been able to identify MV RNA in samples from patients with PD [152][153][154].…”
Section: Otosclerosis and Paget's Disease Of Bonementioning
confidence: 99%
See 2 more Smart Citations
“…No wild-type sequences were obtained, which argues against vaccination being responsible for a delay in OS presentation [151]. In PD, some nucleotides differed from the published vaccine strain, although when five of these were examined more closely [152], they were due to errors in the sequence used for comparison. Others have not been able to identify MV RNA in samples from patients with PD [152][153][154].…”
Section: Otosclerosis and Paget's Disease Of Bonementioning
confidence: 99%
“…In PD, some nucleotides differed from the published vaccine strain, although when five of these were examined more closely [152], they were due to errors in the sequence used for comparison. Others have not been able to identify MV RNA in samples from patients with PD [152][153][154]. The situation in OS is equally unresolved, as some have provided evidence that MV RNA is present in bone samples [140,143,155] and others have not been able to confirm these data [156].…”
Section: Otosclerosis and Paget's Disease Of Bonementioning
confidence: 99%
See 1 more Smart Citation
“…The hypothezised paramyxovirus origin of these inclusions is still debated. (14)(15)(16)(17)(18)(19)(20)(21)(22) Epidemiologic studies have indicated a role for genetic factors in at least a subset of the cases. (23)(24)(25)(26)(27)(28) Some families were reported with a clear autosomal mode of inheritance.…”
mentioning
confidence: 99%
“…PDB is characterized by a localized increase in osteoclast activity leading to excessive focal resorption of bone, followed by the replacement of normal marrow by vascular and brous connective tissue, and disorganized formation of new bone (1,5). Although the cause of PDB is unknown (1,5), several studies strongly suggest the involvement of a genetic component (6,7), and a role for paramyxoviruses has been suggested ( (8), but see (9)) in the etiology of this disorder. Upregulation of interleukin 6 secretion and receptor expression by pagetic bone and marrow cells together with their hypersensitivity to the effects of 1,25 dihydroxyvitamin D 3 , and the role of the receptors for the activation of NFkB (RANK) in the regulation of osteoclast formation could explain the pathological activity of osteoclasts (1,8).…”
mentioning
confidence: 99%